Report on the 2nd international summit on software engineering education, co-located with ICSE2003. - Thompson, J. Barrie (Software engineering notes.)
Work is being undertaken to produce the Software Engineering volume for the ACM/IEEE-CS Computing Curriculum. The prime aim of this Summit was to provide a forum in which early draft chapters of the Software Engineering volume could be used and evaluated by a peer group of academics and industrialists. The objectives and expected outputs for the Summit are outlined and an overview of the presentations that were made is given. The operation and results of a series of participative activities are then described. These were concerned with evaluating the draft chapters and in particular the proposed guidelines for developing Software Engineering academic programmes. Information is also presented on a proposal to restructure the guidelines. Finally some general conclusions are presented.